2018
DOI: 10.1111/mpp.12759
|View full text |Cite
|
Sign up to set email alerts
|

A Meloidogyne graminicola C‐type lectin, Mg01965, is secreted into the host apoplast to suppress plant defence and promote parasitism

Abstract: Summary C‐type lectins (CTLs), a class of multifunctional proteins, are numerous in nematodes. One CTL gene, Mg01965 , shown to be expressed in the subventral glands, especially in the second‐stage juveniles of the root‐knot nematode Meloidogyne graminicola , was further analysed in this study. In vitro RNA interference targeting Mg01965 in the preparasitic juveniles significantly reduced their ability to inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…Our comparative transcriptomic data also showed that M. graminicola relies on the secretion of a set of effector proteins, in addition to CWDEs or peptidases, to establish infection within rice, whether susceptible or resistant cultivars. Effectors are produced by pathogens to facilitate parasitism and a small amount of M. graminicola secreted proteins have been described [ 11 , 12 , 13 , 14 , 15 ]. Mining the M. graminicola transcriptome returned eight novel candidate effectors in addition to those previously described in Petitot et al [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our comparative transcriptomic data also showed that M. graminicola relies on the secretion of a set of effector proteins, in addition to CWDEs or peptidases, to establish infection within rice, whether susceptible or resistant cultivars. Effectors are produced by pathogens to facilitate parasitism and a small amount of M. graminicola secreted proteins have been described [ 11 , 12 , 13 , 14 , 15 ]. Mining the M. graminicola transcriptome returned eight novel candidate effectors in addition to those previously described in Petitot et al [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like MgPDI and Me-TCTP , MgGPP is another effector that may be involved in the suppression of defense reactions of the host cell to promote parasitism [ 11 ]. Among the M. graminicola genes highly expressed in pre-J2s, Mg448 encodes a C-type lectin that could also be involved in overcoming the host defenses as reported for Mg01965 [ 14 ] and for the cyst nematode, Heterodera glycines [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lectin calreticulin [210,211] Mi-CRT secreted by Meloidogyne incognita [212] can inhibit the PAMP-triggered immunity (PTI) elicited by ELF18 that derives from the N-terminal of bacterial elongation factor-Tu. The C-type lectin Mg01965 secreted by M. graminicola can suppress the PTI induced by flg22 which is a PAMP from the N-terminal of bacterial flagellin [131]. The above two lectins are unlikely to mask oligosaccharides, since carbohydrate residues are absent in ELF18 and flg22.…”
Section: Pathogen Lectinsmentioning
confidence: 99%
“…Interesting results were also obtained for RKN lectin, which was experimentally demonstrated to be secreted into host plants as an effector, e.g., Mg01965 from M. graminicola. This protein is released during the early stages of infection and accumulates in the apoplast, where it can suppress PTI, possibly by binding to certain apoplastic sugars and by interfering with sugar signals (Zhuo et al 2019). Effector proteins can also be conserved between some economically important Meloidogyne species, such as M. hapla, M. incognita, and M. graminicola, as described in the example of the Msp18 protein (Grossi-de-Sa et al 2019).…”
Section: Role Of Rkn Effector Proteins In Host Plant Defense Responsesmentioning
confidence: 99%